Efektivitas Sosialisasi PHBS Di SDN Mentor 2 Sebagai Upaya Mencegah Peningkatan Angka Stunting - Rifqi Aji Saputra; Lisa Dwi Yuliana; Hanin Kaulika Ulma; Aura Febrianti Sugianto; Hassyati Sabrina; Kalvin Edo Wahyudi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Clean and Healthy Living Behavior (CLHB) has a major influence on people's living habits related to several aspects including: thoughts, habits, actions, and the environment. Stunting activities in Mentor Village are more focused on the age range of babies and toddlers through posyandu activities than with elementary school students, not a few elementary school students do not receive gradual monitoring regarding stunting. This study aims to determine the effect of clean and healthy living behavior on stunting in toddlers in Mentor Village. The targets in the socialization activity were Mentor I and II Elementary School students, with a total of 50 students. The aim is to provide further education regarding the dangers of stunting with the target of elementary school students. The method is used through 4 stages namely observation, planning stage, socialization and evaluation. Data collection technique is by using a questionnaire in the form of pre-test and post-test. The results of the questionnaire showed an increase in children's understanding related to clean and healthy living behavior (CLBH) where initially the level of children's understanding of CLBH before the socialization was held was 27% and after the socialization activities carried out it increased to 91%. There was an increase in students' understanding of the importance of CLBH by 64% indicating that CLBH socialization activities had a positive effect on increasing students' understanding of the importance of CLBH.